PENTINGNYA KUALITAS LAYANAN DALAM MENINGKATKAN KEPUASAN DAN LOYALITAS PELANGGAN INDIHOME BANJARMASIN - Tarman Effendi; Sari Maharani; Linda Permanasari (INTEKNA informasi teknik dan niaga, 2023)
This study aims to determine the effect of the quality of Indihome service providers in Banjarmasin on customer satisfaction and loyalty. Quantitative research method used in this study. Questionnaires with a Likert scale were distributed to 99 users of Indihome services in Banjarmasin. The sampling method used was convenience sampling by distributing questionnaires at Indihome outlets, Banjarmasin. The data obtained is then processed using path analysis. The findings of this study indicate that the variables reliability and empathy have a significant effect on customer satisfaction. Furthermore, it was also found that the reliability variable also had a significant effect on consumer loyalty